2013
DOI: 10.1113/expphysiol.2013.073353
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of endothelial dysfunction by flow‐mediated dilatation in men on long‐term androgen deprivation therapy for prostate cancer

Abstract: New FindingsAndrogen deprivation therapy (ADT) in men with prostate cancer has been linked to an increased incidence of cardiovascular events and mortality, but the underpinning mechanisms are unclear. Endothelial dysfunction is considered a precursor for cardiovascular disease. Previous studies have reported variably on the association between ADT and endothelial function. This blinded case-control study examined endothelial function, using high-resolution ultrasound to measure flow-mediated dilatation (FMD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 48 publications
0
16
0
2
Order By: Relevance
“…In contrast, Gilbert and colleagues studied men with prostate cancer treated with ADT and controls matched for sex, age, and body mass index. 22 Similarly, the ADT‐treated men had significantly lower testosterone levels compared with controls (12 versus 533 ng/dL). In this study, however, brachial artery endothelium‐dependent vasodilation was lower in men with prostate cancer treated with ADT (3.9%) compared with matched controls (5.9%).…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, Gilbert and colleagues studied men with prostate cancer treated with ADT and controls matched for sex, age, and body mass index. 22 Similarly, the ADT‐treated men had significantly lower testosterone levels compared with controls (12 versus 533 ng/dL). In this study, however, brachial artery endothelium‐dependent vasodilation was lower in men with prostate cancer treated with ADT (3.9%) compared with matched controls (5.9%).…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, endothelial function improved in older men following 3 months of ADT [76]. However, these data are inconsistent with a case-control study that showed that brachial artery FMD was reduced in older men with prostate cancer treated with ADT compared to men without prostate cancer that were matched for age, physical activity, and comorbid CVD and body composition [77]. Discrepancies in the literature could be explained by differences in participant characteristics (age, presence/absence of comorbidities), length of androgen deficiency, and/or in the methodological assessment of FMD, including occlusion placement (upper arm vs lower arm occlusion), and in the analysis of the peak FMD response post cuff deflation (i.e., pre-determined time point vs. continuous).…”
Section: Menmentioning
confidence: 93%
“…However, the high incidence of premature cardiac events on ADT suggests that any cardioprotective effects of HDL may be offset by the adverse effects of ADT on other CVD risk factors. Evidence for the effects of ADT on vascular function in humans has been mixed, with reports of increased arterial stiffness and loss of endothelial cell function in some studies (13)(14)(15) , but not in others (35,41) . There is evidence, exclusively from animal models, (96) Messing et al (2006) (ECOG/EST 3886) (97) Bolla et al (2010) (EORTC 22863) (98) Schröder et al (2009) (EORTC 30846) (99) Studer et al (2006) (EORTC 30891) (100) Efstathiou et al (2009) (RTOG 85-31) (39) Roach et al (2008) (RTOG 86-10) (17) Denham et al (2011) (TROG 96.01) (101) Overall Test for heterogeneity: Q = 5 .…”
Section: Classic Metabolic Syndromementioning
confidence: 99%
“…These findings were soon corroborated by further primary studies, and a highly publicised metaanalysis of observational prospective cohort studies that showed GnRH agonists to be associated, unequivocally, with an increased risk of fatal and non-fatal CVD (12) . These associations have been linked to the adverse effects of ADT on body composition, insulin sensitivity and other cardiometabolic risk factors described below (6) , and also to the specific effects of GnRH agonists in precipitating cardiac events by promoting vascular dysfunction (13)(14)(15) and destabilising atherosclerotic plaque (16) . Nevertheless, RCT have generally failed to substantiate a direct, and thus causal, link between ADT/GnRH agonists and cardiac mortality (17)(18)(19)(20)(21) (Fig.…”
mentioning
confidence: 99%